2004
DOI: 10.1348/1359107041557066
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a tailored lifestyle self‐management intervention in patients with Type 2 diabetes

Abstract: Objectives. The aim of the present study was to develop, implement and evaluate a brief intervention to improve adherence to the recommended lifestyle changes for patients with Type 2 diabetes, in particular to help patients to reduce the total amount of fat consumed and to increase lifestyle physical activity levels.Design and method. A brief, tailored lifestyle self-management intervention for patients with Type 2 diabetes was evaluated in a randomized controlled trial. One hundred participants (aged 40 -70 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
147
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(153 citation statements)
references
References 61 publications
(53 reference statements)
5
147
0
1
Order By: Relevance
“…The findings of this study showed significantly increased exercise behaviors after participating in the selfmanagement program. This finding is similar to a previous study which reported that self-management intervention significantly increased exercise behaviors (Clark, Hampson, Avery, &Simpson, 2004). Several factors that contributed to patients actively performing exercise behavior included:…”
Section: Analysis Of the Dietary And Exercise Self-management Supportsupporting
confidence: 91%
“…The findings of this study showed significantly increased exercise behaviors after participating in the selfmanagement program. This finding is similar to a previous study which reported that self-management intervention significantly increased exercise behaviors (Clark, Hampson, Avery, &Simpson, 2004). Several factors that contributed to patients actively performing exercise behavior included:…”
Section: Analysis Of the Dietary And Exercise Self-management Supportsupporting
confidence: 91%
“…The remaining collection was further analysed in-depth and a total of 12 articles, which reported detail relating to the process of intervention delivery, were included in the final analysis [28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Articlesmentioning
confidence: 99%
“…Education that is culturally relevant (Brown et al 2002;Anderson-Loftin et al 2002) and tailored to the needs and abilities (Clark et al 2004;Two Feathers et al 2007) of the patient has been shown to be effective in improving health outcomes. In sub-Saharan Africa there is a paucity of data or literature on structured, tailored NE programmes targeting individuals with diabetes mellitus.…”
Section: Problem Statementmentioning
confidence: 99%